Unusual massive bone marrow fibrosis in acute promyelocytic leukemia following arsenic trioxide therapy. Issue 2 (2015) - Venkatesan, S.; Purohit, Abhishek; Ahuja, Ankur; Chandra, Dinesh; Aggarwal, Mukul; Amrita, R.; Kumar, Ravi; Mahapatra, Manoranjan; Pati, Hara P.; Tyagi, Seema
Abstract: Bone marrow fibrosis has been associated with different types of non-neoplastic conditions like granulomatous and autoimmune diseases and a variety of neoplastic disorders such as acute megakaryoblastic leukemia, Hodgkin lymphoma, non-Hodgkin lymphoma and myeloproliferative neoplsms. Therapy induced fibrosis is a rare phenomenon. Here we report a case of an incidentally diagnosed acute promyelocytic leukemia (APL) with t (11;17) which was treated with arsenic trioxide (ATO) for 45 days. However, the patient did not go into remission and developed massive fibrosis of bone marrow. Literature search does not reveal such documented marrow fibrosis following therapy with ATO in a case of APL. Highlights: During pre-op evaluation for hysterectomy in a 44 year old, a high TLC was noted. APL with 45 X, − X, t (11;17)(q23;q21) was diagnosed on bone marrow examination. Treated with ATO, day+45 bone marrow biopsy revealed diffuse fibrosis. Case is reported for this unusual feature of ATO-induced bone marrow fibrosis.